Behind That Intimidating Exterior: A Tribute to “Uncle Michael” Scriven - Davidson, E. Jane (Journal of MultiDisciplinary Evaluation, 2024)
Former student and close colleague of the late Michael Scriven's for 26 years, Jane Davidson shares some insights into his personal side to shed light on where he was coming from as an evaluation theorist.